Analytical and numerical investigation of natural rubber bearings incorporating U-shaped dampers behaviour for seismic isolation. (15th September 2021) - Nguyen, Xuan Dai; Guizani, Lotfi
Highlights: U-shaped damper is an efficient energy dissipating device for seismic-resistant design. Analytical and numerical formulation of the in-plane and out-of-plane U-Damper behaviour. Prediction formulas for the in-plane and out-of-plane stiffness and strengths of the U-Damper. U-Dampers can be flexibly combined to elastomeric bearings for optimal seismic isolation designs. Abstract: Although Natural Rubber Bearings (NRBs) constitute a reliable and cost-effective conventional bearing system, they are rarely used for seismic isolation because of their low damping. There are various seismic isolation systems based on NRB, but they mostly have multiple drawbacks (cost, capacity, environmental, etc.). The U-shaped damper (UD) is an efficient energy dissipating device used in seismic-resistant design. However, no guidelines or procedures are available to understand its behaviour nor for design purposes. This paper presents an analytical and numerical investigation of the cyclic behaviour of the NRB system combined with UDs that allow to increase the systems' damping capacity and seismic performance. An analytical study of the UD is performed to predict its initial elastic parameters and numerical models are developed to study the nonlinear behaviour of the NRB-UDs, under large cyclic loadings. A set of UDs and NRBs subjected to cyclic loadings are then studied to investigate their behaviour and the effect of different geometric, loading and design parameters. Results show that the UD significantly dissipates vibration energy based on its large plastic deformations and achieves comparable and predictable performances corresponding to the in-plane and out-of-plane loading directions. Its cyclic behaviour depends on geometrical parameters and material yield stress. The developed analytical formulas provide a reliable estimation of initial elastic parameters of UD, which is essential for the selection and sizing of preliminary designs of the devices. The NRB-UDs systems show a high energy dissipation capacity with stable hysteresis behaviours in any direction. Further, the performance of these devices can be easily adjusted by varying the geometry, number and cross-section of UDs, making them an effective solution that meets a wide range of seismic isolation design requirements in high and moderate seismic areas.